Overexpression of chitinase PbChia1 from Plasmodiophora brassicae improves broad-spectrum disease resistance of Arabidopsis - Yanli Zhao; Chao Li; Xingfu Chen; Jiasen Cheng; Jiatao Xie; yang lin; Yanping Fu; Daohong Jiang; Tao Chen (Virulence)
Chitinase plays an important role in plant resistance against chitin-containing pathogens through hydrolysis of chitin. Clubroot caused by Plasmodiophora brassicae is a major disease for cruciferous crops and vegetables worldwide. The cell wall of P. brassicae resting spores contains chitin. Chitinase is regarded as capable of improving plant resistance to fungal diseases. However, there has been no report about the function of chitinase in P. brassicae. Here, wheat germ agglutinin staining and commercial chitinase treatment demonstrated that chitin is a functional component in P. brassicae. In addition, Chitinase PbChia1 was identified by chitin pull-down assay combined with LC-MS/MS. PbChia1 was found to be a typical secreted chitinase, which could bind chitin with chitinase activity in vitro. PbChia1 could significantly decrease the resting spores of P. brassicae and therefore relieve the severity of clubroot symptom, with a biocontrol effect of 61.29%. Overexpression of PbChia1 in Arabidopsis thaliana improved its resistance to P. brassicae, increased host survival rate and seed yield, enhanced PAMPs-triggered reactive oxygen species burst, MAPK activation and expression of immune-related genes. PbChia1 transgenic plants also showed resistance to other pathogens, such as biotrophic bacterium Pst DC3000, necrotrophic fungi Sclerotinia sclerotiorum and Rhizoctonia solani. These findings indicate that chitinase PbChia1 is a candidate gene that can confer broad-spectrum disease resistance in breeding.